2016
DOI: 10.17511/ijmrr.2016.i09.16
|View full text |Cite
|
Sign up to set email alerts
|

Ossicular status in patients operated for chronic suppurative otitis media

Abstract: Introduction: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the middle ear and mastoid cavity, which presents with recurrent ear discharge through a tympanic perforation. The WHO has classified India as a country with highest prevalence ( > 4%) requiring urgent attention to deal with a massive public health problem. CSOM is often associated with a bone eroding process which occurs due to the presence of cholesteotoma, granulation tissue or both. Methods: This study was conducted in a dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Sharma et al also had a similar result where ossicular-necrosis was maximum when X-ray mastoid showed a cavity in the mastoid. None of the patients with a cellular mastoid had ossicular disruption (5). In sclerotic X-ray there is involvement of mastoid air cells which is attributed to the bone eroding process which has higher changes of ossicular necrosis.…”
Section: Duration Of Disease With Hearing Thresholdmentioning
confidence: 90%
“…Sharma et al also had a similar result where ossicular-necrosis was maximum when X-ray mastoid showed a cavity in the mastoid. None of the patients with a cellular mastoid had ossicular disruption (5). In sclerotic X-ray there is involvement of mastoid air cells which is attributed to the bone eroding process which has higher changes of ossicular necrosis.…”
Section: Duration Of Disease With Hearing Thresholdmentioning
confidence: 90%
“…The most common type of perforation encountered in our study was medium central perforation in 44% of cases followed by large central perforation in 37% of cases. Sharma et al 14 observed the most common type of perforation was central with an incidence of 69.77%. Kamal et al 15 found an incidence of central perforation in COM of 93% in their study population of 203.…”
Section: ) Age Distribution Of Patientsmentioning
confidence: 96%
“…The most common type of perforation encountered in our study was central perforation in 72% of cases followed by subtotal perforation in 28% of cases. Sharma et al 12 observed the most common type of perforation was central with an incidence of 69.77%. Kamal et al 13 found an incidence of central perforation in CSOM of 93% in their study population of 203.…”
Section: Types Of Ossicular Involvementmentioning
confidence: 96%